Effect of Cacao on Plasma F2-Isoprostane Level, CD34 and ICAM-1 Expression of Coronary Arteries in Cigarette Smoking Exposed Rats - Dina Helianti; Soetjipto; Widjiati; I Ketut Sudiana (Institute of Medico-legal Publications Pvt Ltd, 2021)
This research aimed to evaluate cardioprotective effects of cacao in smoking exposure condition that the effects were mediated through the anti-oxidant pathway by measure plasma F2-isoprostane level, Endothelial Progenitor Cell (EPC) enhancement by expression of CD34, while dysfunction endothelial condition was measured by expression of ICAM-1 in coronary arteries. This study subjected rats, divided into four groups: the normal control group (2 ml of aqua bidest, air exposure); the cigarette control group (2 ml of aqua bidest, cigarette smoke); cacao group 1 (1205 mg/kg BW/day, cigarette smoke); cocoa group 2 (2410 mg/kg BW/day, cigarette smoke). The oxidant biomarker, F2-isoprostane level was assessed using ELISA; CD34, and ICAM-1 expression in coronary arteries by immunohistochemistry. Cacao 1205 mg/kg BW/day significantly decreases plasma F2-isoprostane level, and ICAM-1 expression of coronary arteries in cigarette smoking exposed rat (p < 0.05) but there was not a significant increases CD34 (p < 0.05). Cocoa in cigarette smoke-exposed rats can prevent endothelial dysfunction through decrease F2-isoprostane but not increase CD34. The results of this study can be used as a basis for preventing endothelial dysfunction due to cigarette smoke by using cacao.